MURSAL HADEETHS IN MUSANNAF OF ABD RAZZAQ IN THE CHAPTER OF JUMUAH (FRIDAY PRAYER): A CRITICAL ANALYSIS - Cut Linda Marheni (Jurnal As-Salam, 2019)
The purpose of this research is to identify and study the mursal (stopped) hadeeth (prophet tradition) in the mentioned chapter of the Musannaf, in order to know which of them can be raised to the level of Hasan lighairih (hadeeth whose final verdict is good because of support of its witnesses and follow-up), which is can be accepted. The study is done to both of their sanad (chain of transmitters ) and matn (the body text of hadeeth), using the theories of hadeeth science. This study was done by firstly, analyzing the conditions of their ruwat (narrators), then evaluating the shawahid (the same hadeeth that is narrated through the different chain as witnesses ) and mutaba'at (follow-ups). The research finds that most of the narrators of those hadeeths mursal are thiqah (trustworthy ), and all of four mursal hadeeths are acceptable, for they can be raised to the level of hasan lighairih. This finding supports the importance of the Musannaf as a sufficient encyclopedia of hadeeths and Islamic jurisprudence for one who seeks the verification of Islamic law, though it does not have the standard that all the hadeeths it contains must be shahih (sound), but the weak hadeeths in it are potential to be upgraded to the accepted level.